Pengaruh Latihan Menggunakan Resistance Band dan Medicie Ball Terhadap Kekuatan Otot Lengan Atlet Petanque: . - Annisa, Nurul; Riswanto, A. Heri; Hidayat, Rachmat; Nur, Suaib; Sihombing, Binsar Hasudungan (Jurnal Porkes, 2025)
This study aims to determine the effect of training using resistance bands and medicine balls on improving arm muscle strength among petanque athletes at Universitas Muhammadiyah Palopo. The research employed an experimental design with two groups and a pretest-posttest approach. The subjects consisted of 20 petanque athletes who were divided into two groups. The data collection technique used was a test, and the research instrument employed to measure the arm muscle strength of petanque athletes at Universitas Muhammadiyah Palopo was the push-up test. Data analysis was conducted using the SPSS program. The results showed that both training methods had a significant effect on improving arm muscle strength. The group that underwent training with the medicine ball showed a higher average increase in arm muscle strength, with pretest results of 26.20 and posttest results of 32.90, compared to the group that trained using the resistance band, which obtained pretest results of 22.80 and posttest results of 28.30. These findings indicate that training with a medicine ball is more effective in increasing arm muscle strength among petanque athletes at Universitas Muhammadiyah Palopo. It can be concluded that training using resistance bands and medicine balls has a positive effect on improving the arm muscle strength of petanque athletes.